TEACHER AND STUDENT’S INTERACTION BY USING FOREIGN LANGUAGE INTERACTION (FLINT) - Fathya Delona Pratiwi; Chairuddin Chairuddin; Makhroji Makhroji; Evi Zulida; Fadlia Fadlia (Universitas Samudra, 2019)
The purposes of this research were to describe how was the teacher and student’s interaction and to identify the categories of FLINT were used in English class at SMAN 1 Langsa. The research used qualitative design with the object was teacher- students interaction during the class. The subjects of the research were an English teacher and 30 students at a second-year class. The interaction in the classroom revealed that the teacher interacted with students by being cheerful, good natured, patient, not irritable, having good teaching skill, friendly, companionable, knowledgeable, building good communication, interested in students, understandable, and impartial. The students did most of the role but less increased in planning their own learning, mentoring and learning from other students. Furthermore, the communication that happened in the learning process applied all categories of talk as mentioned in FLINT system. The result of the research showed that the pattern of interaction was mostly started by the teacher with utterance of teacher talk was 424 times in a meeting, while the students talk produced 299 times. Asking questions was the most category occurred with 192 times. The least frequently category was using ideas of students which was only 2 utterances produced by the teacher. In student talk categories, student initiation was the most occurred with 142 times and confusion was the least category used with only 11 times. Based on the result above, it can be suggested for the teacher to increase using ideas of student’s category, the teacher should use more students’ ideas in order to make them understand and less confused while teacher is explaining the topic of the lesson.